Programmed cell cycle arrest is required for infection of corn plants by the fungus Ustilago maydis - Castanheira, Sónia (2014)
Ustilago maydis is a plant pathogen that requires a specific structure called infective filament to penetrate the plant tissue. Although able to grow, this filament is cell cycle arrested on the plant surface. This cell cycle arrest is released once the filament penetrates the plant tissue. The reasons and mechanisms for this cell cycle arrest are unknown. Here, we have tried to address these questions. We reached three conclusions from our studies. First, the observed cell cycle arrest is the result of the cooperation of at least two distinct mechanisms: one involving the activation of the DNA damage response (DDR) cascade; and the other relying on the transcriptional downregulation of Hsl1, a kinase that modulates the G2/M transition. Second, a sustained cell cycle arrest during the infective filament step is necessary for the virulence in U. maydis, as a strain unable to arrest the cell cycle was severely impaired in its ability to infect corn plants. Third, production of the appressorium, a structure required for plant penetration, is incompatible with an active cell cycle. The inability to infect plants by strains defective in cell cycle arrest seems to be caused by their failure to induce the appressorium formation process. In summary, our findings uncover genetic circuits to arrest the cell cycle during the growth of this fungus on the plant surface, thus allowing the penetration into plant tissue.